The Challenges of Leadership in Indonesia in Implementing the Digital Transformation of Community 5.0 in the Context of Improving MSME Capacity - Mohammad Aliardo (Ilomata International Journal of Management, 2022)
The development of information and communication technology, which has now entered the industrial revolution 4.0, has received a new challenge, namely society 5.0 as conveyed by Japanese Prime Minister Shinzo Abe in 2017, which is to combine all aspects of people's lives in the development of digital technology intelligence. The COVID-19 pandemic is a momentum for disruption and changes in people's lifestyles on a larger scale towards a digital society. Leadership is one of the factors that will encourage or hinder the implementation of the digital transformation of society 5.0, including in terms of increasing the capacity of MSMEs in Indonesia. This study uses a qualitative research method, namely by making direct observations and using a question form.